Proceedings of the 2nd International Conference on Contemporary Education, Social Sciences and Humanities (ICCESSH 2017) 2017
DOI: 10.2991/iccessh-17.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Research on Current Situation of Overseas Vietnamese Students and Its Policy Improvement

Abstract: Abstract-It is of great importance to explore the current situation of overseas Vietnamese students and policy improvement, in order to improve the management level of overseas Vietnamese students. Research methods like statistical method, inductive method and policy analysis method are applied to conclude the current situation of overseas Vietnamese students, analyze factors influencing the ambition of them and predicaments in studying abroad, and then propose adjusting study-abroad policy of Vietnamese gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…At present, there is no effective policy from government to attract overseas graduates to return. A MOET survey indicates 70% of self-funded overseas students are willing to work in a developed country (Vo & Shi, 2017). Study has shown that 100% of international graduates want to stay in the host country to study and work, regardless of their economic status (Pham, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is no effective policy from government to attract overseas graduates to return. A MOET survey indicates 70% of self-funded overseas students are willing to work in a developed country (Vo & Shi, 2017). Study has shown that 100% of international graduates want to stay in the host country to study and work, regardless of their economic status (Pham, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, ad hoc estimation was found from various sources. Some secondary sources specified the number 63,703 in 2006 (Kuroda et al, 2018), 40,000 in 2006~2007 and 130,000 in 2016~2017 (Vo & Shi, 2017), and to 200,000 in 2018 (L. H. N. Tran, 2019). Figure 2 shows number of Vietnamese international students according to estimation from the MOET in Mar.…”
Section: Current Situation Of Vietnamese International Students Abroadmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there are a number of studies related to students 'overseas study published in international newspapers that are only accessible from the learners' side. Vo's (2017) want to gain better qualifications in order to improve job prospects. Nghia ( 2019) also studies Vietnamese students' motivation to study abroad, confirming that students want to achieve better professional qualifications for the chance to settle.…”
Section: Literaturementioning
confidence: 99%
“…Currently, there is no research in Vietnam on factors influencing the decision of parents to send their children to study abroad. In the country, a few papers study the factors that affect learners' decisions to study abroad (Do & Nguyen, 2020;Nghia, 2019;Vo, 2017;Sen, 2015;Tu & Hang, 2016). Overseas research also focuses on the determinants of students' study abroad (Kakkad & Nair, 2015;Mpinganjira, 2009).…”
Section: Introductionmentioning
confidence: 99%